The Interaction Effects of Homeschooling and Pandemic-Related Worries on Chinese Parents’ Mental Health: A Cross-Sectional Study - Xiaohan Liu; Ning Huang; Mingqi Fu; Naijun Cheng; Jing Guo (Mental Illness)
Conclusion: Homeschooling is significantly associated with Chinese parents’ psychological symptoms. Parental job-related worries are found to moderate the association between homeschooling and parental psychological symptoms. School intervention programs should concern more about children’s negative homeschooling learning status.